Conscious Sedation Versus General Anesthesia for Transcatheter Aortic Valve Replacement: Insights from the National Cardiovascular Data Registry Society of Thoracic Surgeons/American College of Cardiology Transcatheter Valve Therapy Registry. Issue 22 (28th November 2017) - Hyman, Matthew C.; Vemulapalli, Sreekanth; Szeto, Wilson Y.; Stebbins, Amanda; Patel, Prakash A.; Matsouaka, Roland A.; Herrmann, Howard C.; Anwaruddin, Saif; Kobayashi, Taisei; Desai, Nimesh D.; Vallabhajosyula, Prashanth; McCarthy, Fenton H.; et al.
Abstract : Background: Conscious sedation is used during transcatheter aortic valve replacement (TAVR) with limited evidence as to the safety and efficacy of this practice. Methods: The National Cardiovascular Data Registry Society of Thoracic Surgeons/American College of Cardiology Transcatheter Valve Therapy Registry was used to characterize the anesthesia choice and clinical outcomes of all US patients undergoing elective percutaneous transfemoral TAVR between April 1, 2014, and June 30, 2015. Raw and inverse probability of treatment-weighted analyses were performed to compare patients undergoing TAVR with general anesthesia with patients undergoing TAVR with conscious sedation on an intention-to-treat basis for the primary outcome of in-hospital mortality, and secondary outcomes including 30-day mortality, in-hospital and 30-day death/stroke, procedural success, intensive care unit and hospital length-of-stay, and rates of discharge to home. Post hoc falsification end point analyses were performed to evaluate for residual confounding. Results: Conscious sedation was used in 1737/10 997 (15.8%) cases with a significant trend of increasing usage over the time period studied ( P for trend<0.001). In raw analyses, intraprocedural success with conscious sedation and general anesthesia was similar (98.2% versus 98.5%, P =0.31). The conscious sedation group was less likely to experience in-hospital (1.6% versus 2.5%, P =0.03) and 30-day death (2.9% versus 4.1%, P =0.03). Conversion from conscious sedation to general anesthesia was noted in 102 of 1737 (5.9%) of conscious sedation cases. After inverse probability of treatment-weighted adjustment for 51 covariates, conscious sedation was associated with lower procedural success (97.9% versus 98.6%, P <0.001) and a reduced rate of mortality at the in-hospital (1.5% versus 2.4%, P <0.001) and 30-day (2.3% versus 4.0%, P <0.001) time points. Conscious sedation was associated with reductions in procedural inotrope requirement, intensive care unit and hospital length of stay (6.0 versus 6.5 days, P <0.001), and combined 30-day death/stroke rates (4.8% versus 6.4%, P <0.001). Falsification end point analyses of vascular complications, bleeding, and new pacemaker/defibrillator implantation demonstrated no significant differences between groups after adjustment. Conclusions: In US practice, conscious sedation is associated with briefer length of stay and lower in-hospital and 30-day mortality in comparison with TAVR with general anesthesia in both unadjusted and adjusted analyses. These results suggest the safety of conscious sedation in this population, although comparative effectiveness analyses using observational data cannot definitively establish the superiority of one technique over another. Abstract : Supplemental Digital Content is available in the text.